Barriers and facilitators to maintaining confidentiality for HIV and AIDS patients in OR Tambo, Eastern Cape - Qotoyi, Ntombesitatu; Madolo, Agrinette N. (Curationis (Pretoria), 2025)
Background Healthcare practitioners are required to keep patient information private, though sharing is sometimes necessary for patient care, risking confidentiality breaches that can compromise privacy rights. Professional nurses lead HIV prevention, treatment, and care services, but issues like loss to follow-up and confidentiality breaches leading patients to move between clinics to hide their status pose challenges. Objectives This study explored factors influencing professional nurses’ ability to maintain confidentiality in primary healthcare facilities in OR Tambo, Eastern Cape, aiming to develop intervention strategies. Method A qualitative, descriptive, contextual design was used. Nineteen purposively sampled professional nurses participated in semi-structured interviews until data saturation. Interviews were audio-recorded, transcribed verbatim, and thematically analysed using Tesch’s method. Results Findings revealed that confidentiality is impacted by resource shortages, limited knowledge, negative attitudes, and inadequate training. Challenges vary across facilities, but nurses recognize the importance of confidentiality. Participants suggested the need for ongoing training on guidelines and consent procedures to uphold confidentiality. Conclusion Strengthening confidentiality in HIV care requires comprehensive strategies, including staff empowerment, infrastructure improvements, and initiatives to positively influence staff attitudes. Contribution These insights can guide the development of targeted interventions, inform curriculum enhancements, and support future research initiatives.